Construction and validation of students’ drop out scale (2014)
This study constructed and validated a measure for students’ dropout from secondary school programme. The Students’ Dropout Scale (SDS) is a 25-items instrument developed according to the frame work of the social sciences literature on concepts of dropout. Descriptive survey research design was employed. Four hundred dropouts randomly selected using random sampling techniques within Ibadan metropolis were administered the SDS and Emotional Intelligence Scale (EIS). Principal Components and confirmatory factor analyses resulted to a seven component model of SDS. For further purification of data, items with factor loading less than 0.30 and those with more than 0.4 on two or more factors were removed. The instrument has high internal consistency, and adequate construct and discriminant validity. The subscales of SDS were: Self Ability, Self Ignorance, Parents’ Role, Self Desire, Individual Preference, School Relationship and Antisocial Behaviours. The implications of the findings were discussed.